Refinements in the Techniques of 2-Stage Breast Reconstruction. (June 2016) - Freeman, Matthew D.; Vemula, Rahul; Rao, Rahul; Matatov, Tim S.; Strong, Amy L.; Tandon, Ravi; Chaffin, Abigail E.; Jansen, David A.
Abstract : Background: Two-stage breast reconstruction with tissue expanders is one of the most common plastic surgery procedures. Acellular dermal matrix (ADM) has become popular for its ability to improve expansion parameters and aesthetics, albeit with a higher complication profile. We present data that support redefining 2-stage reconstruction to include tissue expanders regardless of final reconstructive modality to act as a bridge. Furthermore, we show that cooperation with the ablative surgeon and technical refinements support ADM omission from the first stage of reconstruction. Methods: We retrospectively reviewed charts from the senior author's (D.A.J.) private practice over a 10-year follow-up period. Inclusion criteria included all women over 18 years who underwent mastectomy and had a tissue expander placed immediately or in a delayed fashion and successfully completed tissue expansion and are finished with the second stage of reconstruction or awaiting second stage of reconstruction. Demographic data, tissue expander filling data, final reconstruction, aesthetic outcome, and complications were tabulated. Results: A total of 118 women (165 breasts) met inclusion criteria. There were no statistically significant differences in initial fill volume ( P = 0.094), number of visits until final expansion ( P = 0.677), or final fill volume ( P = 0.985) between the ADM and non-ADM cohorts. In addition, non-ADM patients had superior aesthetic scores with respect to defects other than scarring ( P = 0.015), projection ( P = 0.013), and inframammary fold quality ( P = 0.009). Fifteen percent of women decided to change desired final reconstruction modality during the tissue expansion phase. Conclusions: This reconstructive algorithm emphasizes surgical cooperation between the ablative and reconstructive surgeon, improved technique, and patient education. This focus translates into maintained tissue expansion, aesthetically pleasing results, and allows for the omission of ADM from reconstruction.